A multisensory centrifugal neuron in the olfactory pathway of heliothine moths. Issue 1 (22nd November 2012) - Zhao, Xin‐Cheng; Pfuhl, Gerit; Surlykke, Annemarie; Tro, Jan; Berg, Bente G.
Abstract We have characterized, by intracellular recording and staining, a unique type of centrifugal neuron in the brain olfactory center of two heliothine moth species; one in Heliothis virescens and one in Helicoverpa armigera. This unilateral neuron, which is not previously described in any moth, has fine processes in the dorsomedial region of the protocerebrum and extensive neuronal branches with blebby terminals in all glomeruli of the antennal lobe. Its soma is located dorsally of the central body close to the brain midline. Mass‐fills of antennal‐lobe connections with protocerebral regions showed that the centrifugal neuron is, in each brain hemisphere, one within a small group of neurons having their somata clustered. In both species the neuron was excited during application of non‐odorant airborne signals, including transient sound pulses of broad bandwidth and air velocity changes. Additional responses to odors were recorded from the neuron in Heliothis virescens. The putative biological significance of the centrifugal antennal‐lobe neuron is discussed with regard to its morphological and physiological properties. In particular, a possible role in multisensory processes underlying the moth's ability to adapt its odor‐guided behaviors according to the sound of an echo‐locating bat is considered. J. Comp. Neurol. 521:152–168, 2013. © 2012 Wiley Periodicals, Inc.